A Geospatial Analysis of the Rhinologist Workforce in the United States. Issue 4 (July 2022) - Hassanin, Samir; Kshirsagar, Rijul S.; Steele, Toby O.; Liang, Jonathan
Background: Six percent of practicing otolaryngologists identified by the American Academy of Otolaryngology - Head and Neck Surgery (AAO-HNS) are rhinologists. This is the first study to investigate both the distribution of rhinologists in the United States and the sociodemographic characteristics that may predict their practice locations. Objective: We aim to describe the geospatial distribution of the rhinology workforce and analyze sociodemographic characteristics associated with practice distribution. Methods: We conducted a cross-sectional study of 662 rhinologists queried from the 2020 American Rhinologic Society (ARS) database. Rhinologist practice addresses were compared with ZIP code tabulation area (ZCTA) sociodemographic data from the 2010 US Census Bureau and from the 2014 to 2018 American Community Surveys. Geospatial mapping and multivariate statistics were employed to visualize rhinologist practice locations and analyze which community characteristics were associated with greater densities of rhinologists in ZCTAs. Results: The largest and smallest densities of rhinologists were in coastal areas and in the Central and Midwestern US, respectively. Population characteristics that significantly predicted a higher number of practicing rhinologists included: greater percentage of non-citizens and greater educational attainment (p < 0.001). Population characteristics that significantly predicted a lower number of practicing rhinologists included: greater percentage of self-identified white/Caucasians, median household income, and greater percentage of population aged 65 or older (p < 0.001). Conclusion: Disparities in healthcare access in the US is evident and applies to rhinologic subspecialty care. Through visual geospatial analysis, we demonstrate the distribution of rhinologists and the population characteristics that may be predictive of whether patients have access to rhinological care.